Investigating the Color Distribution of Young and Old Galaxies Using Observations from SDSS - Qasim, Shahad M.; Mahdi, Hareth S. (Iraqi Journal of Science, 2024)
This research aims to investigate the color distribution of a huge sample of 613654 galaxies from the Sloan Digital Sky Survey (SDSS). Those galaxies are at a redshift of 0.001 - 0.5 and have magnitudes of g = 17 - 20. Five subsamples of galaxies at redshifts of (0.001 - 0.1), (0.1 - 0.2), (0.2 - 0.3), (0.3 - 0.4) and (0.4 - 0.5) have been extracted from the main sample. The color distributions (u-g), (g-r) and (u-r) have been produced and analysed using a Matlab code for the main sample as well as all five subsamples. Then a bimodal Gaussian fit to color distributions of data that have been carried out using minimum chi-square in Microsoft Office Excel. The results showed that the color distributions of the main sample and all subsamples are bimodal. This indicates that the color distribution is an ideal tool to differentiate between young and old galaxies. The young and blue star-forming galaxies are represented by one of the two peaks, while the old and red non-star-forming galaxies are represented by the other peaks of the color distribution.